Going beyond science-policy interaction? An analysis of views among intergovernmental panel on climate change actors. Issue 1 (2nd January 2021) - Thoni, Terese; Livingston, Jasmine E.
ABSTRACT: Scholarly literature on science-policy interaction is typically divided between advocating that science and policy need to be brought closer together or separated. In a recent article in this journal, Sundqvist and colleagues [Sundqvist et al. (2018) Oneworld or two? Science–policy interactions in the climate field, Critical Policy Studies, 12:4, 448–468] proposed a typology that structures this debate. We use their typology to conduct a text analysis on empirical material from the Intergovernmental Panel on Climate Change's (IPCC) internal consultation on its future. We find that science-policy practitioners are not as divided as the scholarly debate. Moreover, while the typology is a powerful tool in unearthing differences in opinion regarding science-policy interaction, it comes at the price of reductionism. We suggest that a continuum, instead of separate boxes, helps visualize the large spectrum of ideas. However, regardless of type of typology, it is important that the discussion goes beyond the relationship between science and policy, and beyond an unconstructive battle between extremes. It is neither possible nor normatively desirable to demarcate 'science', 'policy' and other actors. Whilst this discussion is of central importance to the IPCC, greater focus should be put on its relationship with society.